PROGRAM PEMBERDAYAAN MASYARAKAT DALAM PENANGANAN STUNTING DI KELURAHAN PANCUR, TAKTAKAN, SERANG BANTEN - Kosasih, Kosasih; Sujana, Nanan (Community Services and Social Work Bulletin, 2023)
Stunting is one of the strategic problems experienced by people in Banten, especially in the Pancur sub-district, Serang, Banten. The socialization and training activity "Stunting Prevention" is a form of implementation of the Real Work Lecture (KKN) theme in Banten. This activity will be carried out in August – September 2023, located in Pancur Village, Taktakan District, Serang City. The stunting prevention outreach and training program is carried out by adopting the knowledge and importance of drinking milk which explains that food consists of carbohydrates, protein, vitamins, minerals and water. Partners involved in the KKN program include children, teenagers, young people, PKK mothers, Posyandu Group and the surrounding community. Furthermore, activities to socialize parenting patterns and meet the nutritional needs of mothers and children need to be increased. Then, training on washing hands using soap by implementing 7 steps on how to wash hands using soap to kill microorganisms went smoothly. The "Lungs of the World" program by planting fruit trees, such as manga, rambutan and longan as a source of oxygen and useful for public consumption. It is hoped that the KKN program will continue to be implemented by Muhammadiyah Tangerang University as a forum for students to actualize knowledge, insight and gain experience to help overcome problems and interact in society.